2000
DOI: 10.1074/jbc.275.3.2003
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA Damage by Vitamin A and Its Derivative via Superoxide Generation

Abstract: Recent intervention studies revealed that ␤-carotene supplement to smokers resulted in a higher incidence of lung cancer. However, the causal mechanisms remain to be clarified. We reported here that vitamin A (retinol) and its derivative (retinal) caused cellular DNA cleavage detected by pulsed field gel electrophoresis. Retinol and retinal significantly induced 8-oxo-7,8-dihydro-2-deoxyguanosine formation in HL-60 cells but not in H 2 O 2 -resistant HP100 cells, suggesting the involvement of H 2 O 2 in cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
2
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(104 citation statements)
references
References 43 publications
3
98
2
1
Order By: Relevance
“…By contrast, lower ROL concentrations 1-5 µM, which are considered to be within the physiological range for Sertoli cells (52) increased neither reactive species production nor proliferation. On the other hand, in human promyelocytic leukemia cells HL-60 concentrations of 2-5 µM have been reported to induce oxidative DNA damage (53). In the present study a dose as low as 0.5 µM ROL, is enough to induce a proliferative response in human cancer cells.…”
Section: Discussionmentioning
confidence: 56%
“…By contrast, lower ROL concentrations 1-5 µM, which are considered to be within the physiological range for Sertoli cells (52) increased neither reactive species production nor proliferation. On the other hand, in human promyelocytic leukemia cells HL-60 concentrations of 2-5 µM have been reported to induce oxidative DNA damage (53). In the present study a dose as low as 0.5 µM ROL, is enough to induce a proliferative response in human cancer cells.…”
Section: Discussionmentioning
confidence: 56%
“…Solovieva et al reported that antioxidants, ascorbic acid (Solovieva et al, 2007) and dithiothreitol (Solovieva et al, 2008), exhibit cytotoxicity via H 2 O 2 generation. Relevantly, it has been reported that vitamins A (Murata & Kawanishi, 2000) and E (Yamashita et al, 1998) and catechins (Oikawa et al, 2003) induce DNA oxidation through H 2 O 2 generation during their oxidation. H 2 O 2 is a long-lived reactive oxygen species which plays an important role in biomacromolecular damage induced by various chemical compounds (Kawanishi et al, 2001;Hirakawa et al, 2002).…”
Section: Catalytic Decomposition Of Hydrogen Peroxide By Metal Nanopamentioning
confidence: 99%
“…These findings showed that the Pt nanoparticles have the highest catalytic activity for H 2 O 2 decomposition in the metal nanoparticles used in this experiment and the activity of Pt nanoparticles is suppressed by modification with Ag. (Yamashita et al, 1998;Murata & Kawanishi, 2000). Indeed, an excess of these antioxidants elevates the incidence of cancer (Nitta et al, 1991;Omenn et al, 1996).…”
Section: Summary and Possible Mechanism Of Hydrogen Peroxide Decomposmentioning
confidence: 99%
“…[107][108][109] An intriguing connection between retinoids and the senescence response is the fact that retinoids promote the formation of reactive oxygen species (ROS) in cells. 110 High levels of ROS can be detected in several types of senescence and treatment with hydrogen peroxide or culturing cells on high oxygen also trigger senescence (for a review see Ref. 111).…”
Section: Spotlightmentioning
confidence: 99%